Methods and effectiveness of surgical antisepsy of the hands in the preoperative (Research, Society and Development, 2021)
Objective: This research aims to seek and compare the methods used in performing surgical hand antisepsis in the preoperative period and to evaluate which method is more appropriate and effective for the use of the surgical team, aiming at a safer patient care. Methodology: This is an exploratory literature review with a qualitative approach, where searches were made for materials published between 2010 and 2019 in the “Google Academic” database, where materials that supported the development of this research were found. Results: All methods and techniques used to perform surgical hand antisepsis present satisfactory results in the elimination of resident and transient flora, however, antisepsis performed with alcoholic solution was the most effective. Conclusion: With the results found in this research, it is concluded that it contributes to the quality of the service provided by the surgical team and with the nurse as the manager of the operating room, serving as a basis for decision making in light of the needs and the way more adequate preoperative surgical hand antisepsis, providing quality care and greater safety for the surgical patient.